Perceived risk and its role in the influence of brand awareness on purchase intention: study of Shopee users - Sri Rahmi; Gunawan Bata Ilyas; Hasmin Tamsah; Abdul Razak Munir (Jurnal Siasat Bisnis, 2022)
Purpose: This research aimed to analyze the role of perceived risk in the relationship between brand awareness and purchase intention. This research is important because the perceived risk of online purchasing can influence consumer purchasing behavior.Design/methodology/approach: This research used an explanatory study with a quantitative approach. The research was conducted on 112 Shopee users in Makassar City. Data were collected through an online questionnaire. The data collected were analyzed using the Structural Equation Modelling (SEM) with the AMOS application and the Sobel Test to test the indirect relationship.Findings: Risk, financial risk, time risk, delivery risk, and privacy risk were essential elements forming perceived risk. Brand awareness had a positive influence on purchase intention. Perceived risk was a variable that mediated the influence of brand awareness on purchase intention.Originality/value: The results of this research indicated that the more aware consumers are of a brand, the negative perceptions of the brand will appear due to the ease with which information was disseminated and accepted by consumers. Perception of risk is a factor that can reduce consumer buying interest. Consumer purchase intention towards a known brand will decrease if the brand is perceived as having a high risk.Research limitation: This research was conducted on most students who did not yet have stable financial capabilities. For further studies, we suggest using respondents who have better financial ability to provide a more tangible measurement of purchasing ability.Practical implication: Results showed that perceived risk could reduce the influence of brand awareness on purchase intention. Thus, minimizing risk, ensuring the absence of perceived negative things before choosing a brand, and ensuring consumer comfort in using a brand were factors encouraging purchase intention.